Hepatic steatosis and advanced hepatic fibrosis are independent predictors of long‐term mortality in acute myocardial infarction. Issue 4 (6th January 2023) - Chin, YipHan; Lim, Jieyu; Kong, Gwyneth; Ng, Cheng Han; Goh, Rachel; Muthiah, Mark; Mehta, Anurag; Chong, Bryan; Lin, Chaoxing; Chan, Kai En; Kong, William; Poh, Kian Keong; et al.
Abstract: Aim: To examine the prevalence and prognosis of hepatic steatosis and fibrosis in post‐acute myocardial infarction (AMI) patients. Methods: Patients presenting with AMI to a tertiary hospital were examined from 2014 to 2021. Hepatic steatosis and advanced hepatic fibrosis were determined using the Hepatic Steatosis Index and fibrosis‐4 index, respectively. The primary outcome was all‐cause mortality. Cox regression models identified determinants of mortality after adjustments and Kaplan–Meier curves were constructed for all‐cause mortality, stratified by hepatic steatosis and advanced fibrosis. Results: Of 5765 patients included, 24.8% had hepatic steatosis, of whom 41.7% were diagnosed with advanced fibrosis. The median follow‐up duration was 2.7 years. Patients with hepatic steatosis tended to be younger, female, with elevated body mass index and an increased metabolic burden of diabetes, hypertension and hyperlipidaemia. Patients with hepatic steatosis (24.6% vs. 20.9% mortality, P  < .001) and advanced fibrosis (45.6% vs. 32.9% mortality, P  < .001) had higher all‐cause mortality rates compared with their respective counterparts. Hepatic steatosis (adjusted hazard ratio 1.364, 95% CI 1.145‐1.625, P  = .001) was associated with all‐cause mortality after adjustment for confounders. Survival curves showed excess mortality in patients with hepatic steatosis compared with those without ( P  = .002). Conclusions: Hepatic steatosis and advanced fibrosis have a substantial prevalence among patients with AMI. Both are associated with mortality, with an incrementally higher risk when advanced fibrosis ensues. Hepatic steatosis and fibrosis could help risk stratification of AMI patients beyond conventional risk factors.